Association of methylenetetrahydrofolate reductase gene polymorphisms and maternal folic acid use with the risk of congenital heart disease - Zhong, Taowei; Song, Xinli; Liu, Yiping; Sun, Mengting; Zhang, Senmao; Chen, Letao; Diao, Jingyi; Li, Jinqi; Li, Yihuan; Shu, Jing; Wei, Jianhui; Zhu, Ping; et al. (Frontiers in Pediatrics, 2022)
Abstract Background: To systematically evaluate the association of MTHFR genetic polymorphisms, maternal folic acid intake, and the time when folic acid intake was started with the risk of congenital heart disease (CHD) and investigated the role of their interaction on infant CHD risk in Chinese populations. Method: A case-control study involving 592 CHD cases, 617 health controls, and their mothers was performed. The exposures of interest were single nucleotide polymorphisms (SNPs) of the MTHFR gene, maternal folic acid use, and the time when folic acid use was started. We applied the logistic regression model to explore the strength of association. Results: Our findings showed that mothers lacking folic acid intake had a significantly higher risk of CHD in offspring (aOR=2.00; 95%CI: 1.34-2.98). Mothers who started to use folic acid from the first trimester of the fetation (aOR=1.65; 95% CI: 1.22–2.23) or from the second trimester of the fetation (aOR=7.77; 95% CI: 2.52-23.96), compared with those starting to use folic acid from 3 months previous to the conception, were at a significantly higher risk of CHD in offspring. Genetic variants at rs2066470 (AA vs. GG: aOR=5.09, 95%CI: 1.99-13.03), rs1801133 (AA vs. GG: aOR=2.49, 95%CI: 1.58-3.93), and rs1801131 (TG vs. TT: aOR=1.84, 95%CI: 1.36-2.50; GG vs. TT: aOR=3.58, 95%CI:1.68-7.63) were significantly associated with the risk of CHD based on the multivariate analysis. Additionally, statistically significant interactions between maternal folic acid intake and genetic variants of the MTHFR gene at rs1801133 and rs1801131 were observed. Conclusion: An association of maternal folic acid intake and the time when intake was started with the risk of CHD in offspring was found. What’s more, maternal folic acid fortification may help counteract partial of the risks of CHD in offspring attributable to MTHFR genetic mutations.